Rotary Club of Madras : open defecation free communities project - Parmar, Ashis Jalote, (SAGE Knowledge. Cases., 2015)
It was June 24, 2015. A thanksgiving function was organized by the Rotary Club of Madras (RCM), Chennai, as the Presidency of S. N. Srikanth was coming to a close at the end of his one year tenure. The RCM was a voluntary organization of business and professional leaders providing humanitarian services. The past President of Rotary International (RI), Rotarian (Rtn) Kalyan Banerjee was the chief guest of this function, and soon to take charge as the Chairperson of the Board of Trustees of the Rotary Foundation. One of the most significant achievements during Srikanth's tenure had been the successful execution of the Open Defecation Free (ODF) Communities project in Amarampedu village in Gummidipoondi block, in the state of Tamil Nadu.